Development of Worksheets for High School Biology Student-Based On Critical Thinking Skills on the Circulation System Concept - Ellen Nabella; Muhammad Zaini; Aulia Ajizah (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2020)
Learning in the 2013 curriculum requires a learning process that refers to the scientific approach. The teacher becomes the centre of learning in the current educational problems, students accepting learning as an abstract does not have the opportunity to develop their thinking skills. The purpose of this study is to develop a valid, practical, and effective Educator Worksheet (LKPD). This study uses the Tessmer design method, which consists of (1) expert review; (2) one-to-one; and (3) small group. Subjects of expert opinion research included two biology education lecturers and one high school biology teacher. Individual test subjects were three students educated. The small group test subjects were six students who were educated. The type of data obtained includes data effectiveness expectations. The results obtained from the effectiveness of expectations based on students' critical thinking skills in working on LKPD have very good categories (including analysis, reference, and exploration) and have good categories (including interpretation and self-regulation). Interpersonal skills (collaborating) and intrapersonal skills (conscientious) students have very good categories with scores of interpersonal skills and intrapersonal skills 86.33%.AbstrakPembelajaran pada Kurikulum 2013 menuntut adanya proses pembelajaran yang mengacu pada pendekatan saintifik. Guru menjadi pusat pembelajaran pada persoalan pendidikan yang terjadi saat ini, peserta didik menerima pembelajaran secara abstrak tidak memiliki kesempatan untuk mengembangkan keterampilan berpikirnya. Tujuan penelitian ini yaitu mengembangkan Lembar Kerja Peserta Didik (LKPD) yang valid, praktis, dan efektif. Penelitian ini menggunakan metode desain Tessmer, yang terdiri dari: 1) expert review; 2) one-to-one; dan 3) small group. Subjek penelitian pendapat pakar meliputi dua orang dosen pendidikan biologi dan satu orang guru biologi SMA. Subjek uji perorangan adalah tiga orang peserta didik. Subjek uji kelompok kecil adalah enam orang peserta didik. Jenis data yang didapatkan meliputi data keefektifan harapan. Hasil didapatkan dari keefektifan harapan berdasarkan keterampilan berpikir kritis peserta didik dalam mengerjakan LKPD memiliki kategori sangat baik (meliputi analisis, inferensi, dan eksplanasi) serta memiliki kategori baik (meliputi interpretasi dan pengaturan diri). Keterampilan interpersonal (bekerjasama) dan keterampilan intrapersonal (teliti) peserta didik memiliki kategori sangat baik dengan skor keterampilan interpersonal dan keterampilan intrapersonal 86,33%.